EFEKTIVITAS PROGRAM SIM ONLINE PADA SATUAN LALU LINTAS GUNA MENINGKATKAN PELAYANAN PUBLIK DI POLRES PURWAKARTA - Ibrahim, Yuril (Advances in Police Science Research Journal, 2020)
ABSTRACT Korlantas conducted innovation at Satlantas Polres Purwakarta in online SIM registration to cut bureaucracy of making new and extending SIMs. Until February 2020, the number of users is still not in accordance with the goal. This research aimed to find out online SIM Registration Program, the effectivity of using online SIM registration, the influencing factors. This research was conducted with a qualitative approach, using subjective meaning research methods, and data collection techniques by interviewing, observing, and studying documents. The results of the study found that the use of the online SIM Registration Program for the system, implementing competencies, internal supervision, number of implementers, and guarantee of public service safety has not met the standards. Factors that support the organization internally are leadership policies, a good work culture, rewards in the form of reward and punishment, routine socialization, while for external organizations there are high expectations from the community related to efforts to improve public services. There are two factors that inhibit internally, namely human resource factors and factors on the internet server program network, while externally the level of public knowledge. It is recommended to educate and train personnels, adding facilities and infrastructures to support the performance of personnel in the service of an online SIM program, to improve the stability of an online SIM program server and internet network in the Purwakarta area, in the form of a special outlet for online SIM registration, work the same in the socialization of the program with radio and print media